1992
DOI: 10.1113/jphysiol.1992.sp019331
|View full text |Cite
|
Sign up to set email alerts
|

Activation of N‐methyl‐D‐aspartate receptors by L‐glutamate in cells dissociated from adult rat hippocampus.

Abstract: SUMMARY1. Single channel recording techniques were used to study the ion channel openings resulting from activation of N-methyl-D-aspartate (NMDA) receptors by the agonist glutamate. Patches were from cells acutely dissociated from adult rat hippocampus (CAI). Channel activity was studied at low glutamate concentrations (20-100 nM) with 1 puM-glycine, in the absence of extracellular divalent cations. A. J. GIBB AND D. COLQUHOUN supports the idea that the NMDA receptor channel gating has the properties of a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
193
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(241 citation statements)
references
References 57 publications
(148 reference statements)
43
193
5
Order By: Relevance
“…The high conductance state observed (65 pS) may be the result of chelation of free Ca 2+ and Mg 2+ by EDTA used in all steps of the isolation and reconstitution of the protein complex. Gibb and Colquhoun [25] have reported the presence of high conductances (> 60 pS) for neuronal NMDARs upon chelation of free extracellular Ca 2+ and Mg 2+. All protein preparations used in the present studies were subjected to extensive dialysis against EDTA.…”
Section: Properties Of the L-glu-activated Ion Channelsmentioning
confidence: 99%
“…The high conductance state observed (65 pS) may be the result of chelation of free Ca 2+ and Mg 2+ by EDTA used in all steps of the isolation and reconstitution of the protein complex. Gibb and Colquhoun [25] have reported the presence of high conductances (> 60 pS) for neuronal NMDARs upon chelation of free extracellular Ca 2+ and Mg 2+. All protein preparations used in the present studies were subjected to extensive dialysis against EDTA.…”
Section: Properties Of the L-glu-activated Ion Channelsmentioning
confidence: 99%
“…The existence of very occasional much longer intervals (of a second or longer, see Fig. 2A) suggests that the bursts may be grouped into clusters (Gibb & Colquhoun, 1992). With 98 mm Nae, burst durations were best described by the sum of two exponentials with longer bursts the most prevalent, a feature common to other ion channels (Magleby & Pallota, 1983 b;Colquhoun & Sakmann, 1985).…”
Section: Bursting Properties Of Main State General Propertiesmentioning
confidence: 99%
“…A window with a width of three points corresponding to 0'3 ms was shifted over the singlechannel record. The mean and variance of the data points within each window were calculated and a 'levels' histogram constructed as described previously (Mistry, Tripathi & Chapman, 1996 (Colquhoun & Sakmann, 1985;Gibb & Colquhoun, 1992) which was obtained using the second and third closed-time constants (r2 and T3, respectively). Bursts were defined as an opening or group of openings separated by closures shorter than the specified critical closed time, so that closures greater than TC were classed as interburst gaps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly this is meaningless (valid by nature) for the single channel records that are recorded from nonzero steady state currents as the origin of time is meaningless. This assumptions has been validated for many channels with an acceptable level of accuracy [10,14,15] However for some inactivating channels under some special conditions it has been observed that the open duration may have a small dependency on the time that channel has opened [16]. We term the probability density function of the open duration…”
Section: Theoretical Methodsmentioning
confidence: 99%